Physiological adaptations during endurance training below anaerobic threshold in rats - De Araujo, Gustavo Gomes; Papoti, Marcelo; Delbin, Maria Andréia [UNESP]; Zanesco, Angelina [UNESP]; Gobatto, Claudio Alexandre (Springer Nature, 2013)
To assess the effects of continuous exercise training at intensities corresponding to 80 and 90 % of the lactate minimum test (LM), we evaluated antioxidant activity, hormone concentration, biochemical analyses and aerobic and anaerobic performance, as well as glycogen stores, during 12 weeks of swimming training in rats. One-hundred rats were separated into three groups: control (CG, n = 40), exercise at 80 (EG80, n = 30) and 90 % (EG90, n = 30) of LM. The training lasted 12 weeks, with sessions of 60 min/day, 6 days/week. The intensity was based at 80 and 90 % of the LM. The volume did not differ between training groups (Ẋ of EG80 = 52 ± 4 min; Ẋ of EG90 = 56 ± 2 min). The glycogen concentration (mg/100 mg) in the gastrocnemius increased after the training in EG80 (0.788 ± 0.118) and EG90 (0.795 ± 0.157) in comparison to the control (0.390 ± 0.132). The glycogen stores in the soleus enhanced after the training in EG90 (0.677 ± 0.230) in comparison to the control (0.343 ± 0.142). The aerobic performance increased by 43 and 34 % for EG80 and EG90, respectively, in relation to baseline. The antioxidant enzymes remain unchanged during the training. Creatine kinase (U/L) increased after 8 weeks in both groups (EG80 = 427.2 ± 97.4; EG90 = 641.1 ± 90.2) in relation to the control (246.9 ± 66.8), and corticosterone (ng/mL) increased after 12 weeks in EG90 (539 ± 54) in comparison to the control (362 ± 44). The continuous exercise at 80 and 90 % of the LM has a marked aerobic impact on endurance performance without significantly biomarkers changes compared to control. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Biomarkers; Endurance; Performance; Rats; Training